Person-Environment Fit Perceptions and Satisfaction at Work (Malaysian Management Journal, 2003)
This study aims to fulfil two literature gaps in the person-environment fit theory, in particular, relating to the supply-value fit or S-V fit. Firstly, previous research in S-V fit tended to look mainly at autonomy and supervision style. However, there appears to be no reported research that has simultaneously investigated in a single study, the effects of the discrepancy between the perceived and desired levels of work quantity, variety, power, responsibility and concentration required for the job. This study aims to fill that gap. This study examines the discrepancy between the supplies and values of work quantity, variety, power, responsibility and concentration, and its relationship with satisfaction at work. Secondly, the S-V fit theory has been relatively established in developed countries such as America and Britain. However it would be interesting to discover whether the theory is also applicable among civil service workers in a small isolated town, in a developing country such as Malaysia. Questionnaires were distributed and collected from one hundred respondents working in a government department in a small town of Gua Musang in Peninsular Malaysia. Support for the S-V fit theory was obtained, as results suggested that the greater the discrepancy between the supplies and values of work quantity, variety, power, responsibility and concentration required at work, the lesser was the satisfaction. The implication therefore was that if managers were desirous of improving satisfaction of their workers, they should ensure that their workers receive neither too much nor too little work variety, power, responsibility and concentration at work-for either state can result in lower satisfaction.